An Audit of Patterns of Unnatural Deaths: an Autopsy Based Study - Waheed All Nayhoon, Semen Ahmed Farsi Kazi, Naveed All Qadri, Raffia Arain Shahid Kamran, Aisha Rasheed Sheikh , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2018)
Objective: To audit the medicolegal patterns and causes of unnatural deaths conducted at Liaquat University hospital. Methods: This descriptive study was performed in the Postmortem suit, Liaquat University Jamshoro/Hyderabad and Medico-legal section olLiaquat Uni‘.-ersity Hospital Hyderabad from December 2014 to October 2016. A sample of 100 autopsy cases was sorted for the findings of study interest according to the study aims. objects. Post mortem reports, emergency notes, referral notes and police papers were used for the data collection. Hospital emergency department notes were taken for severely injured victims that later on died an.d autopsied. Data variables were typed on Excel sheet. Variables of study interest were analyzed by descriptive statistics. Results: Of 100 autopsy sample, homicidal, suicidal and accidental deaths were noted in 51',.0, 24% and 20• respectively ( P=0.001). Firearm injury (46%), road traffic deaths (10%), hanging (10(' ). blunt (7%) and sharp edged weapons (6°..0) account for large number of cases. Homicidal (51%) was most common pattern ofd.eath and firearm injury (40%) was most common mode. Conclusion: The present study reports most common pattern of death was homicidal noted in 51% of cases and commonest mode of death was firearm weapons. Use of illegal firearm weapons needs urgent action. Timely provision of justice, strict adhesion to traffic rules and social values should be realized to the masses.